Factors influencing young indonesian consumer’s online utilization intention case study: Effect of technology acceptance, electronic word of mouth, and price setting on university of lampung student’s purchase intention of Netflix streaming service (Asian Journal of Economics and Business Management, 2023)
The purpose of this study is to investigate the factors that influence young consumers' intentions to subscribe to Netflix. While previous research has looked at the factors that influence subscription intention in the context of other online entertainment platforms, there has been a lack of research that looks specifically at the factors that influence Netflix subscription intention among young adults. Therefore this research aims to fill the research gap by exploring possible factors influencing young Indonesian consumers’ online utilization intention. This research intends to determine whether there is an effect of technology acceptance, electronic word of mouth, and price setting on the University of Lampung students’ intention to subscribe to Netflix. This research was quantitatively conducted, and samples are 107 active students of the University of Lampung gathered through questionnaires. This research applies the IBM SPSS testing design to implement this objective. The multiple linear regression analysis is used as the method of this research. The statistical results after the hypothesis testing show that each variable, namely: technology acceptance, electronic word of mouth, and price setting, has a p-value < alpha (5%). This means that hypotheses one, two, and three are valid, and it can be concluded that young consumers' Netflix subscription intention is positively influenced by technology acceptance, electronic word-of-mouth, and pricing. Price setting has the most significant impact, followed by technology acceptance and electronic word-of-mouth. Netflix can adopt this research to make decisions that will increase the number of subscribers and reduce the number of unsubscribing customers by focusing on technological features and experience, content offerings, and pricing packages.